Consumo dos frutos de Davilla rugosa (Dilleniaceae) por aves numa área de cerrado em São Carlos, Estado de São Paulo - Francisco, Mercival Roberto; Galetti, Mauro [UNESP] (My University, 2002)
Fruits have been considered an important feeding resource used not only by frugivorous birds, but also by omnivore and some insectivore species. In the present paper we are reporting the behavior of birds consuming fruits of Davilla rugosa (Dilleniaceae). Handling behavior and visits frequency were analyzed in order to infer about the potential ornithochoric seed dispersal. Focal observations were carried out from October to December 1999 in a cerrado fragment located in São Paulo State, Southeastern Brazil (21°58′S, 47°52′W). In 60 h of field work we recorded 241 visits of 13 passerine bird species consuming the fruits. The mean number of visits per hour and the standard deviation were 4.01 ± 4.88. All of the species were considered potential seed dispersers, since no pulp mashers or seed predators were observed. No temporal difference in visit frequency was found when all of the species were analyzed together or when they were individually considered. Generalist species were responsible for 68.5% of the visits, followed by frugivorous (22.82%) and insectivorous (8.71%). The main potential seed dispersers were Elaenia spp. (Tyrannidae), Tangara cayana (Emberizidae), Empidonomus varius (Tyrannidae), Turdus leucomelas (Muscicapidae) and Vireo chivi (Vireonidae). The high visit frequency observed suggests that D. rugosa fruits may be an important feeding resource for birds in the cerrado ecosystem, in the manner that this plant can be considered in management plans which intent to maintain or rescue bird communities.
Consumption of Davilla rugosa (Dilleniaceae) fruits by birds in a cerrado area at São Carlos, São Paulo State
Keywords: Cerrado; Davilla rugosa; Frugivory; Ornithochory; Seed dispersal; Aves; Dilleniaceae; Elaenia; Emberizinae; Empidonomus varius; Muscicapidae; Passeriformes; Tangara cayana; Turdus leucomelas; Tyrannidae; Vireo; Vireonidae